A tortura continua! : o regime militar e a consolidação do autoritarismo nas instituições de segurança pública - Silveira, Felipe Lazzari da (2014)
This work aims to identify in which degree the continuity of torture today relates to the previous historic periods, mainly the military regime and the process of democratic transition. For that, we adopt the assumption that torture is an authoritarian and extremely violent mechanism that has accompanied the Brazilian history since the colonial times, but was institutionalized during 1964 and 1985, when the military drastically altered the security system of the country and ended up intensifying the violent action pattern of the public security institutions. Using the bibliography and documents researched, we aim to identify the contribution of the military regime and the transitional process to the naturalization of authoritarianism and violence in the Brazilian society, mainly in the public security institutions that, nowadays, keep practicing torture when exercising criminality control. During the research, we have confirmed the hypothesis that the authoritarianism installed in our society, maximized during the dictatorship and not neutralized by the unfinished transitional process, adding to that the problems inherent to the lifestyle in contemporary society, made possible the permanency of a violent action pattern by the public security institutions and, consequently, the continuity of torture in a very similar fashion to the ones verified in the authoritarian period.